Dampak Digitalisasi pada Komunikasi Perusahaan: Tinjauan Sistematis Literatur tentang Adaptasi dan Perubahan Budaya Kerja - Julianta Pratama Pinem (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In today's modern and digital era, all movements are required to be carried out more quickly and precisely with digital technology as the main key. Digitalization has changed the way of communication within companies, allowing information to be conveyed and received quickly, anytime and anywhere. Companies need to adapt to changes in technology and work culture to remain competitive, although digitalization also brings challenges in communication and interaction. A work culture that supports innovation is important to create an environment that is adaptive to technological change and motivates employees to contribute to the innovation process. This research uses library methods. The library method is a method of collecting data by reviewing relevant books, literature, notes and reports without having to use primary or secondary data from the field. Literature studies are important for exploring theories related to research topics and helping researchers understand the current state of the field of science being researched. The research results show that digitalization has brought significant changes in HR management and company work culture, accelerating the flow of information and decision making. Digital technology increases collaboration and work efficiency, as well as facilitating more efficient communication processes. HR managers must adapt to new roles that require digital skills and strong managerial abilities. While digitalization provides many benefits, such as increased recruitment efficiency and in-depth analytics, challenges such as data security and the impact on employee mental health also arise